الصوتیات والمرئیات المتاحة عبر المواقع الاسلامیة : دراسة کمیة ونوعیة - د. فاطمة ابراهیم خمیس (المجلة الدولية لعلوم المكتبات والمعلومات)
This study deals with audiovisual files available on Islamic web sites, And What it involves of Recitations Of The Quran , The Prophet's Biography, Hadith, Fatawa, Fiqh ,Sunna, Anasheed And Prayers , speeches and lessons for scholars and, Sheikhs and preachers. To make comprehensive survey of quantative of audiovisual materials , also subjects, and forms & specifications of audiovisual files . The paper focus on the motivations and behaviors of users consening audiovisual materials available on Internet , also the problems the users are facing , In addition the paper try to determining the best Islamic sites from quality point of view containing audios and videos based on browsers frequency visits to these sites , Finally evaluate those sites technically and. objectively